Integrated Space-Time Dataset Reveals High Diversity and Distinct Community Structure of Ciliates in Mesopelagic Waters of the Northern South China Sea - Sun, Ping; Huang, Liying; Xu, Dapeng; Warren, Alan; Huang, Bangqin; Wang, Ying; Wang, Lei; Xiao, Wupeng; Kong, Jie (Frontiers in Microbiology, 2019)
Little is known about diversity distribution and community structure of ciliates in mesopelagic waters, especially how they are related to spatial and temporal changes. Here, an integrative approach, combining high-throughput cDNA sequencing and quantitative protargol stain, was used to analyze ciliate communities collected temporally along a transect from coastal to oceanic regions at depths ranging from the surface to 1000 m. The mesopelagic zone exhibited comparable alpha diversity to surface water which was consistent over temporal variation, with high diversity occurring at the interface with the euphotic zone. Comparison with the northeastern and the western Pacific Ocean revealed consistency of this vertical distribution of ciliates across oceanic basins. Mesopelagic ciliates harbored distinct community structure without significant seasonal differences, with the vertical variations driven largely by members of the classes Spirotrichea and Oligohymenophorea. Operational taxonomic units (OTUs) affiliated with Scuticociliatia, Astomatida and Apostomatida, members of which are known to be bacterivorous and/or commensal/parasitic species, were more abundant in mesopelagic waters than above, implying they are an important component of food webs in the mesopelagic zone. A combination of depth, geographic distance and environment shaped the ciliate communities, with depth being the most influential factor. Phylogenetic null modeling analysis further indicated that 57.1% and 33.3% of mesopelagic community variation was governed by dispersal limitation and heterogeneous selection, respectively, due to the marked biochemical and physical gradients down the water column. This suggests that ciliate community structure in the mesopelagic zone is mainly controlled by stochastic processes. Collectively, this study reports mesopelagic ciliates exhibited high diversity and distinct community structure across spatiotemporal scales and informs the mechanisms and processes mediating ciliate assembly in the mesopelagic zone. These should be fully considered in future studies to build a more comprehensive understanding of mesopelagic microbial assemblages.